The Impact of Environmental Innovation, Carbon Emission, and Resource Use on Financial Distress Moderated by Corporate Governance - Hadis, Fajar Sukma; Masyhuri Hamidi; Fajri Adrianto (Management Institute Faculty of Economics Universitas Andalas, 2025)
This study examines the effect of environmental innovation, carbon emission, and resource use on financial distress, with corporate governance as a moderating variable, in companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using purposive sampling, consisting of 15 companies that consistently published sustainability reports and had environmental scores from Refinitiv LSEG, resulting in a total of 75 observations. Secondary data were obtained from financial statements and sustainability reports, and analyzed using panel data regression with the Fixed Effects Model. The findings reveal that environmental innovation has a significant negative effect on financial distress, while resource use has a significant positive effect. In contrast, carbon emission does not significantly affect financial distress. Regarding the moderating role, corporate governance positively strengthens the relationship between environmental innovation and financial distress, indicating that in the short term, high investment costs in green innovation may increase financial pressure. Meanwhile, corporate governance does not significantly moderate the effect of carbon emission on financial distress, but significantly weakens the positive effect of resource use on financial distress. Overall, the results highlight that environmental innovation is crucial in reducing financial risks, efficient resource management must be optimized, and strong corporate governance serves as a key mechanism to enhance the effectiveness of sustainability strategies.